Rational Design of Plasmonic Nanostructures for Biomolecular Detection: Interplay between Theory and Experiments - Fraire, Juan Carlos (2012)
In this work, we report a simple strategy to obtain ultrasensitive SERS nanostructures by selfassembly and bioconjugation of Au nanospheres (NSs). Homodimer aggregates with an interparticle gap of around 8 nm are generated in aqueous dispersions by the highly specific molecular recognition of biotinylated Au NSs to streptavidin (STV), while random Au NS aggregates with a gap of 5 nm are formed in the absence of STV due to hydrogen bonding among biotinylated NSs. Both types of aggregates depict SERS analytical enhancement factors (AEF) of around 107 and the capability to detect biotin concentrations lower than  1012 M. Quite interesting, the AEF for an external analyte, Rhodamine 6G (RH6G), using the dimer aggregates is 1 order of magnitude greater (105) than using random aggregates (around 104). The dependence on the wavelength and the differences of the AEF for Au random aggregates and dimers are rationalized with rigorous electrodynamic simulations. The dimers obtained afford a new type of an in situ self-calibrated and reliable SERS substrate where biotinylated molecules can selectively be ?trapped? by STV and located in the nanogap enhanced plasmonic field. Using this concept, powerful molecular-recognition-based SERS assays can be carried out.The capability of the dimeric structures for analytical applications is demonstrated using SPR spectroscopy to detect biotinylated immunoglobulin G at very low concentrations.fic molecular recognition of biotinylated Au NSs to streptavidin (STV), while random Au NS aggregates with a gap of 5 nm are formed in the absence of STV due to hydrogen bonding among biotinylated NSs. Both types of aggregates depict SERS analytical enhancement factors (AEF) of around 107 and the capability to detect biotin concentrations lower than  1012 M. Quite interesting, the AEF for an external analyte, Rhodamine 6G (RH6G), using the dimer aggregates is 1 order of magnitude greater (105) than using random aggregates (around 104). The dependence on the wavelength and the differences of the AEF for Au random aggregates and dimers are rationalized with rigorous electrodynamic simulations. The dimers obtained afford a new type of an in situ self-calibrated and reliable SERS substrate where biotinylated molecules can selectively be ?trapped? by STV and located in the nanogap enhanced plasmonic field. Using this concept, powerful molecular-recognition-based SERS assays can be carried out.The capability of the dimeric structures for analytical applications is demonstrated using SPR spectroscopy to detect biotinylated immunoglobulin G at very low concentrations.